Assessment of Eucalyptus Stem Diameter Estimation Using Terrestrial Laser Scanning - Rianthakool, Laddawan; Yingdee, Jirawat; Chumsangsri, Theerapong; Sittibal, Detrit (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Stem diameter plays a pivotal role in forest mensuration, encompassing applications in growth assessment, stand density estimation, wood production, and carbon sequestration. Traditionally measured with diameter tape or calipers through ground-based methods, the advent of Terrestrial Laser Scanning (TLS) has introduced a non-destructive 3D modeling technology for precise measurements. In this study, we aimed to assess the accuracy and precision of eucalyptus stem diameter estimation using TLS in comparison to ground-based diameter tape measurement. The results showed an average diameter at breast height (dbh) of 13.840 cm and an average height of 18.5 m for the sample trees. Stem curves from TLS were automatically derived from the 3D Forest program analyses of standing eucalyptus trees. Our analysis reveals that the average Root Mean Square Error (RMSE) for estimated stem diameter using TLS was 4.34 cm for the first ten sections of the tree from the ground. The measurement of stem size in eucalyptus trees using TLS tends to show increased RMSE in the upper sections of the stem. Our research underscores the high accuracy achieved in estimating stem diameters, particularly for the lower portions of the trees, even under light wind conditions.